2016
DOI: 10.1007/s40520-015-0522-1
|View full text |Cite
|
Sign up to set email alerts
|

Balancing benefits and risks of glucocorticoids in rheumatic diseases and other inflammatory joint disorders: new insights from emerging data. An expert consensus paper from the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO)

Abstract: Purpose This consensus review article considers the question of whether glucocorticoid (GC) therapy is still relevant in the treatment of rheumatic diseases, with a particular focus on rheumatoid arthritis (RA), and whether its side effects can be adequately managed. Recent basic and clinical research on the molecular, cellular and clinical effects of GCs have considerably advanced our knowledge in this field. An overview of the subject seems appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 169 publications
(150 reference statements)
0
20
0
Order By: Relevance
“…The ability to tailor interventions to the needs of the patient is a critical element in successful programs targeting older adults. 34 Future studies need to replicate these diverse methods to add strength to current findings.…”
Section: Literature Analysismentioning
confidence: 94%
“…The ability to tailor interventions to the needs of the patient is a critical element in successful programs targeting older adults. 34 Future studies need to replicate these diverse methods to add strength to current findings.…”
Section: Literature Analysismentioning
confidence: 94%
“…An expert consensus statement from the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO) recommends assessment of patients for fracture risk. Bone preserving agents, calcium and vitamin D are useful for preventing GC related fractures [19]. Use of supplements was common and most physicians reported using supplements after 3-6 months of steroid use in our study.…”
Section: Discussionmentioning
confidence: 61%
“…A retrospective study from UK, showed that GC below 5 mg is not associated with elevated risk of mortality [18]. Similarly, short term use of moderate doses are also generally well tolerated [19].…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be assessed for fracture risk and bone preserving agents and be prescribed calcium and vitamin D supplementation (B) [39]. Bisphosphonates remain the first choice of treatment in GC-treated patients with high fracture risk (A) [40].…”
Section: How Long Should Sam Patients Receive Immunosuppressive / Immmentioning
confidence: 99%